Performance Of Commercial Broilers Under Different Intermittant Lighting Programs - Hegde , Ganesh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
An experiment was conducted to study the effect of intermittent lighting program on the performance and carcass yield of commercial broilers. The light treatment from 14 days onwards up to 42 days was given as 23 hr light and 1 hr darkness for continuous light program and 4 hr light and 2 hr darkness intermittently for intermittent light program. The results indicated that there was no significant difference in body weight at 14, 35 and 42 days of age in both treatments. Continuous lighting produced significantly higher body weight at 21 and 28 days of age. Feed conversion efficiency (FCR) did not differ significantly at 14, 21, and 28 days of age. But it was significantly better in intermittent lighting regime after 35 days of age. Carcass yield and drumstick were significantly higher for intermittent lighting treatment. Continuous light treatment produced significantly higher fillets and tenders at 42 days of age.
Keywords: broilers; Continuous light; Intermittent light; body weight; FCR; carcass yield